The Role of Phosphorylation in Synucleinopathies: Focus on Parkinson's Disease - Cavallarin, Nadia; Vicario, Mattia; Negro, Alessandro (CNS & Neurological Disorders - Drug Targets, 2010)
α-Synuclein is a soluble, natively unfolded protein that is highly enriched in the presynaptic terminals of neurons in the central nervous system. Interest in α-synuclein has increased markedly following the discovery of a relationship between its dysfunction and several neurodegenerative diseases, including Parkinson's disease. The physiological functions of α-synuclein remain to be fully defined, although recent data suggest a role in regulating membrane stability and neuronal plasticity. In addition, there is increasing evidence pointing to phosphorylation as playing an important role in the oligomerization, fibrillogenesis, Lewy body formation, and neurotoxicity of α-synuclein in Parkinson's disease. Immunohistochemical and biochemical studies reveal that the majority of α-synuclein within inclusions from patients with Parkinson's disease and other synucleinopathies is phosphorylated at Ser129. α-Synuclein can be phosphorylated in vitro also at Ser87, and three C-terminal tyrosine residues (Tyr125, Tyr 133, and Tyr136). Tyrosine 125 phosphorylation diminishes during the normal aging process in both humans and flies. Notably, cortical tissue from patients with Parkinson's disease-related synucleinopathy dementia with Lewy bodies showed less phosphorylation at Tyr125. While phosphorylation at Ser87 is enhanced in synucleinopathies, it inhibits α-synuclein oligomerization, and influences synuclein-membrane interactions. The possibility that α-synuclein neurotoxicity in Parkinson's disease and related synucleinopathies may result from an imbalance between the detrimental, oligomer-promoting effect of Ser129 phosphorylation and a neuroprotective action of Ser87/Tyr125 phosphorylation that inhibits toxic oligomer formation merits consideration, as will be discussed in this article.
Keywords: transgenic